2020
DOI: 10.1109/access.2020.2979922
|View full text |Cite
|
Sign up to set email alerts
|

Points-of-Interest Recommendation Algorithm Based on LBSN in Edge Computing Environment

Abstract: With the advancement of the Internet of Everything era and the popularity of mobile devices, Location-based Social Networks (LBSN) have penetrated people's lives. People can take advantage of portable edge terminal devices and use the geographic information in LBSN to arrange or adjust their travel plans. However, due to the explosive growth of current Internet applications and users, it has brought greater pressure and operation and maintenance costs to cloud storage. It is a key research direction based on l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 21 publications
(21 reference statements)
0
9
0
Order By: Relevance
“…We would also like to mention that in some works we have found strange statistics that we believe to be inaccurate. For example, in [21], the authors claim to use a Foursquare dataset but the same statistics can be found in [32,47] for a Gowalla dataset. The statistics reported in [98,113] are also strange as they report more users than check-ins (in this case, for a Foursquare dataset).…”
Section: Systematic Review Of Datasets Used In State-of-the-artmentioning
confidence: 99%
“…We would also like to mention that in some works we have found strange statistics that we believe to be inaccurate. For example, in [21], the authors claim to use a Foursquare dataset but the same statistics can be found in [32,47] for a Gowalla dataset. The statistics reported in [98,113] are also strange as they report more users than check-ins (in this case, for a Foursquare dataset).…”
Section: Systematic Review Of Datasets Used In State-of-the-artmentioning
confidence: 99%
“…Those public datasets were widely used in early studies on social networks. Gan and Gao [28], Naserian et al [29], and Cao et al [30] used the Foursquare dataset to verify the applicability of their location-based recommendation systems. Jiao et al [31] used the Gowalla and Foursquare datasets to simulate travel decision-making processes in order to recommend POIs for users.…”
Section: Overview Of Existing Social Network and Lbsnsmentioning
confidence: 99%
“…Liu et al [76] developed the spatiotemporal dilated convolutional generative network for POI recommendation. Cao et al [30] developed a recommendation system based on edge computing using LBSN data.…”
Section: Recommendation Systems Using Data Acquired From Lbsnsmentioning
confidence: 99%
“…We would also like to mention that in some works we have found strange statistics that we believe to be inaccurate. For example, in [21], the authors claim to use a Foursquare dataset but the same statistics can be found in [34,53] for a Gowalla dataset. The statistics reported in [122,141] are also strange as they report more users than check-ins (in this case, for a Foursquare dataset).…”
Section: Systematic Review Of Datasets Used In State-of-the-artmentioning
confidence: 99%